Environmental and cultivar effects on technological quality of the bread wheat (Triticum aestivum L.) produced in the Pampean plain of Argentina - Molfese, Elena Rosa (2021)
The quality of the wheat grain is determined by several factors that lead to different physical, chemical and/or rheological characteristics. The aim of the work was to evaluate the effects of the type of cultivar quality and agricultural region of production on parameters that define the commercial and industrial quality of wheat. A total of 3,486 wheat samples were collected from producer lots. The samples corresponded to commercial cultivars classified according to the quality type following a system used in Argentina, which is based on the combination of commercial and baking quality indicators. These wheat varieties were produced in three different regions according to resource availability (fertility of the soil and average rainfall). The technological quality of the different grain samples and flours was determined by means of physicochemical analyses. The samples from the region of high resource availability with higher productivity and lower industrial quality differed from those from the regions of low and medium resource availability. Grain test weight and ash content were significantly affected by the interaction between the quality group of the cultivars and the region of origin. Grain protein and gluten contents were mainly conditioned by the resource availability of the region. However, the quality of the gluten was genetically conditioned by quality group of the cultivars. As results of the relationships among these parameters, most of the variables of flour quality (color, W, P/L and farinograph stability) would be explained by the interaction between the cultivar and the environment where it was grown.